Media screening and optimization of lactic acid fermentation - Abdul Karim, Mohamed Ismail; Mel, Maizirwan; Jamal, Parveen; Mohamed Salleh, Mohamad Ramlan; Alamin, Noraini (2005)
The screening and optimization of lactic acid production using bacteria L. rhamnosus were successfully carried out in shake flask experiment. Initially eleven variables were screened using Placket Burman Design and result indicated that, the main variables that effected were glucose and peptone. These two most significant variables were then optimized using the Central Composite Design. The correlation between those two variables was analyzed using Response Surface Methodology (RSM). The contour plot indicates that the interactions between these two variables are not much significantly different. The optimization and critical value indicate that the most ideal concentration of glucose and peptone for optimum production of lactic acid in shake flask is 9.80g/l and 9.98g/l, respectively. The maximum growth rate for these bacteria is 0.394 h-1 and the productivity is 0.630 g/g.h.